Percutaneous Transapical Access for Performing Interventional Procedures in Patients with Structural Heart Pathologies: a Single Center Experience - Ditkivskyy, I. O.; Petrov, M. S.; Yashchuk, N. S.; Yermolovych, Y. V.; Cherpak, B. V.; Mazur, O. A.; Tregubova, M. O.; Perepeka, I. A. (Ukrainian Journal of Cardiovascular Surgery, 2020)
The paper describes the experience of percutaneous transapical access (PTA) usage for performing transcatheter structural interventions in 7 patients. Four patients had paravalvular insufficiency of the prosthetic mitral valve, one patient had a reshunt of ventricular septal defect and a pseudoaneurysm in the area of fibrous mitral-aortic continuity. Two patients underwent PTA for diagnostic examination. The visualization methods, planning algorithm, and technique of the procedure have been described. The overall efficiency was 100%, the degree of paravalvular leak was reduced in all treatment procedures. The main reported complication was hemothorax in two cases. In one case, the occluder migrated from the paravalvular fistula channel into the left atrial cavity with subsequent endovascular extraction. The aim. This study was designed to evaluate modern outlooks about the use of PTA during interventions, enhance the available data and extrapolate the authors’ own experience with the development of their own conclusions and recommendations. Materials and methods. To differentiate structural pathology, the initial selection of patients was performed according to the findings of transthoracic and transesophageal ultrasound. The next step in planning of PTA is analysis of computed tomography (CT) data with 3D reconstruction. PTA and subsequent interventions were performed in the hybrid catheterization laboratory after evaluation of CT data, guided by transesophageal echocardiography (TEE), and with the establishment of optimal angles of the angiograph arc for the best fluoroscopic imaging. Besides, in order to avoid trauma of left anterior descending coronary artery, selective angiography was performed. Surgical team support was essential in all cases. Results. The overall efficiency was 100%, reduction of the degree of paravalvular leak was achieved in all treatment procedures. The main reported complication was hemothorax in two cases. In one case, the occluder migrated from the paravalvular fistula channel into the left atrial cavity with subsequent endovascular extraction. Discussion. The subject of our research was PTA for structural interventions. Available data of the world literature shows that this technology has been developed since the end of the last century. The main complications that can be encountered during the intervention by PTA were: hemothorax; hemopericardium/tamponade; rupture of the coronary artery; pneumothorax; arrhythmia; death. In four out of five cases, we used a Lifetech HeartR PDA occluder to close the puncture site of the left ventricular apex. In the fifth case, LifeTech mVSD occluder was used. Conclusions. Correction of structural pathology by routine use of PTA requires a comprehensive approach to the diagnosis of this pathology using transthoracic and transesophageal echocardiography, contrast-enhanced CT and 3D reconstruction. Support of a multidisciplinary team to provide transition to conventional cardiac surgery access in case of periprocedural complications is mandatory. Due to the emergence of specialized implants, as well as the development of imaging techniques, PTA requires attention and further study.